Little doctor training at SDN 4 Kertaharja - Mila Herlina; Gina Nisa Nur Illahi; Serli Sri Putri Sutiaman; Lala Elawati; Alsa Nurina Ayuningtias; Dini Purna Rahman Fauzi; Gunawan Refiadi (Universitas Muhammadiyah Magelang, 2023)
Elementary school-age children are a group at high risk of disease because they are still in the growth and development stage. The lack of understanding about clean and healthy living behavior (PHBS) and its application within the school sphere is the main contributing factor. PHBS is the most basic thing to prevent the onset of a disease. The school health unit (UKS) program can help improve the quality of education, health as well as student achievement. The UKS and PHBS programs need to be synergized with elementary school-age children. The hope is to achieve a healthy school environment, student growth and optimal development. One of the main programs of this community service is smart village through training of little doctors for students of SDN 4 in Kertaharja Village, Pangandaran. The method used is in the form of giving a pre-test at the beginning of the activity, then providing education about PHBS and UKS management. After that, a post-test was carried out on 12 students. According to the evaluation, there is an increase in knowledge from 63.75% to 74.16%. Based on these activities, it can be concluded that there is an increase in students' knowledge after education.